Plastic debris in great skua (Stercorarius skua) pellets corresponds to seabird prey species. Issue 1 (15th February 2016) - Hammer, S.; Nager, R.G.; Johnson, P.C.D.; Furness, R.W.; Provencher, J.F.
Abstract: Plastic is a common item in marine environments. Studies assessing seabird ingestion of plastics have focused on species that ingest plastics mistaken for prey items. Few studies have examined a scavenger and predatory species that are likely to ingest plastics indirectly through their prey items, such as the great skua ( Stercorarius skua ). We examined 1034 regurgitated pellets from a great skua colony in the Faroe Islands for plastics and found approximately 6% contained plastics. Pellets containing remains of Northern fulmars ( Fulmarus glacialis ) had the highest prevalence of plastic. Our findings support previous work showing that Northern fulmars have higher loads of plastics than other sympatric species. This study demonstrates that marine plastic debris is transferred from surface feeding seabird species to predatory great skuas. Examination of plastic ingestion in species that do not ingest plastics directly can provide insights into how plastic particles transfer vertically within the food web. Graphical abstract: Highlights: Plastic was found in regurgitated pellets of great skuas in the Faroe Islands. Most plastic debris occurred in pellets from Northern fulmar prey. Likely great skua plastic consumption is secondary uptake from their seabird prey. This is a first case of vertical transfer of plastic in the North Atlantic food web.